Biomarkers and potential therapeutic targets driving progression of non-alcoholic steatohepatitis to hepatocellular carcinoma predicted through transcriptomic analysis - Hui Fan; Rong Wang; Bin Wen; Jing Xiong (Frontiers in Immunology)
BackgroundNon-alcoholic steatohepatitis (NASH) is the most prevalent chronic liver condition globally, with potential progression to cirrhosis, and even hepatocellular carcinoma (HCC). The increasing prevalence of NASH underscores the urgent need for advanced diagnostic and therapeutic strategies. Despite its widespread impact, effective treatments to prevent the progression of NASH remain elusive, highlighting the critical importance of innovative molecular techniques in both the diagnosis and management of this disease.MethodsSix microarray datasets available in GEO were used to perform Robust Rank Aggregation (RRA) to identify differentially expressed genes (DEGs).We identified 62 robust upregulated genes and 24 robust downregulated genes. These genes were undergone Gene Ontology enrichment analysis and further examination for expression correlation with NAS score. Molecular subtypes were generated using “ConsensusClusterPlus” on identified genes, which were further assessed for tumor stage relevance, expression differences in adjacent and tumor tissues, and impact on survival in TCGA liver cancer patients. Single-cell analysis was then used to explore the genes across different cell types and subgroups as well as cell-type interactions. The clinical utility of predicted core genes was highlighted through decision curve analysis, with emphasis on HCC prognosis. The GDSC database was used to evaluate the relationship between the predicted core genes and drug sensitivity, while the TIDE database was used to evaluate their relationship with immunotherapy.ResultsFour core genes, TREM2, GDF15, TTC39A, and ANXA2, were identified as key to influencing HCC prognosis and therapy responsiveness, especially immune treatment efficacy in NASH-associated HCC.ConclusionThe core genes may act as critical biomarkers driving the progression of NASH to HCC. They are potential novel targets for the diagnosis and treatment of NASH progression, offering innovative perspectives for its clinical management.